(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to determine the effect of employee competence and work motivation on employee performance at the Central Java Provincial Regional Secretary. Data were collected through a survey with 88 respondents. Researchers used primary data obtained from distributing questionnaires via Google Form to employees of the Central Java Provincial Regional Secretary. The technique used in sampling was non-probability sampling. The analytical tool used in this study was SPSS software version 26. Respondents were employees of the Central Java Provincial Regional Secretary. The results of this study are that employee competence has a significant effect on leadership style at the Central Java Provincial Regional Secretariat. Work motivation has a significant effect on leadership style at the Central Java Provincial Regional Secretariat.